Critical Thinking of Future Primary School Teachers as a Pedagogical Problem - Rakhimovna, Toshmatova Ormonoy (International Journal on Orange Technologies, 2022)
The article argues that the system of tools for the formation of critical thinking of future primary school teachers must be consistent with the goals of the formation of the initial stage - the motives. However, even at this stage, methods of influencing other components of critical thinking (forms, content, methods, techniques, self-control, and self-awareness) are shown.